Obciążenia fiskalne gospodarstw rolniczych w zależności od wielkości ekonomicznej oraz typu rolniczego - Forfa, Magdalena (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The aim of the paper is to define the level of fiscal burden in farms in relation european size and type of farming in Mazowsze and Podlasie region, in Poland and also in selected European Union countries. The period of farm investigation covers the years 2004–2008. On the basis of conducted research has been ascertained that farms which had lower economic power (ESU), had the highest level of fiscal burden. In addition, the type of farm – “milk” paid the lowest taxes in relation to their income. Thus, the tax system favors farms, where production is highly dependent on land and high economic strength.